The use of Computer and Pedagogical Technologies in Laboratory Classes in Chemistry - Jurayeva O.B. (Research Parks Publishers, 2022)
The gradual and successful implementation of the national training program in our country is largely due to the activities of students, which increase their professional prestige. Therefore, time requires them to constantly improve their qualifications, acquire modern knowledge and experience in accordance with the high standards of today and creative work.